Towards Quadruple-Play Service: Both Individual and Household Level Analyses on Mobile Bundle - Eun Yu; Jaemin Jung (International Telecommunications Society (ITS), 2018)
Quadruple-play grows worldwide and shows potential to extend the range of telecommunications service from network to content. Mobile bundle enables multichannel strategy integrating home television and mobile display. Since mobile is a personal service, joining a household bundle with mobile is an individual-level choice. However, literature has concentrated on household-level decisions. This paper focuses on economic factors and mobile engagement of individuals as well as household attributes to fill the gap in the research stream about telecommunications bundle. The balanced panel datasets support fixed effect logit models for both households and individuals. The analysis shows that bundle promotes the adoption of a mobile bundle and prevents churn. The installment is the stronger predictor than mobile subscription fee for the adoption of a mobile bundle. The results from mobile engagement factors lead to further researches on the relationship between engagement and telecommunications service.
Keywords: 330; quadruple-play service; telecommunication bundle; mobile engagement; Korean media panel